Internal audit and corporate governance in local government in Tanzania: A case of Mwanza City Council - Njunwa, Florian (Mzumbe University, 2025)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirement for the award of the degree of Master's of Business Administration (MBA-CM) of Mzumbe University 2013